2016
DOI: 10.1016/j.enpol.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying analysis of CO2 emissions, energy consumption, and economic growth nexus: Statistical experience in next 11 countries

Abstract: This paper detects the direction of causality among carbon dioxide (CO 2 ) emissions, energy consumption, and economic growth in Next 11 countries for the period 1972-2013. Changes in economic, energy, and environmental policies as well as regulatory and technological advancement over time, cause changes in the relationship among the variables. We use a novel approach i.e. time-varying Granger causality and find that economic growth is the cause of CO 2 emissions in Bangladesh and Egypt. Economic growth causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(73 citation statements)
references
References 89 publications
7
57
0
Order By: Relevance
“…The evidence of strong pollution abatement policies has already been identified by Shahbaz et al (2016) and , and on the other hand, the pollution abatement policies of BRICS countries have been criticized by Chakravarty and Mandal (2016) and Sinha and Sen (2016). Our results support these evidences, along with the new finding regarding the presence of inverted Nshaped EKC in both of these groups of countries.…”
Section: Estimation Of the Model Without Corruptionsupporting
confidence: 85%
“…The evidence of strong pollution abatement policies has already been identified by Shahbaz et al (2016) and , and on the other hand, the pollution abatement policies of BRICS countries have been criticized by Chakravarty and Mandal (2016) and Sinha and Sen (2016). Our results support these evidences, along with the new finding regarding the presence of inverted Nshaped EKC in both of these groups of countries.…”
Section: Estimation Of the Model Without Corruptionsupporting
confidence: 85%
“…The outcome indicates that a 1% increase in agricultural value added decreases carbon dioxide emissions by 0.38%; a 1% increase in energy consumption increases carbon dioxide emissions by 0.96% and a 1% increase in trade openness increases carbon dioxide emissions by 0.44%. The empirical results are consistent with Shahbaz et al (2016Shahbaz et al ( , 2018. To compare our results with previous studies that utilized FMOLS technique, Liu et al (2017) indicated that a 1% increase in agricultural value added decreases per capita carbon emissions by 0.53%, whereas a 1% increase in per capita non-renewable energy increases per capita carbon dioxide emissions by 0.52% among four ASEAN countries.…”
Section: Long and Short-run Relationshipsupporting
confidence: 83%
“…The empirical results are consistent with Shahbaz et al . (, ). To compare our results with previous studies that utilized FMOLS technique, Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study that has conducted by Shahbaz et al (2016b) to estimate the EKC for CO 2 emissions in N-11 countries by considering CO 2 emissions, energy consumption, and economic growth within the EKC framework. They find the evidence of an inverted U-shaped EKC for all N-11 countries.…”
Section: Economic Growth and Co 2 Emissionsmentioning
confidence: 99%